Efficacy of Polyphenylene Carboxymethylene (PPCM) Gel at Protecting Type I Interferon Receptors Knockout Mice from Intravaginal Ebola Virus Challenge - Olivier Escaffre; Terry L. Juelich; Jennifer K. Smith; Lihong Zhang; Madison Pearson; Nigel Bourne; Alexander N. Freiberg (Viruses)
Ebola virus (EBOV) is one of three filovirus members of the Orthoebolavirus genus that can cause severe Ebola disease (EBOD) in humans. Transmission predominantly occurs from spillover events from wildlife but has also happened between humans with infected bodily fluids. Specifically, the sexual route through infectious male survivors could be the origin of flare up events leading to the deaths of multiple women. More studies are needed to comprehend this route of infection which has recently received more focus. The use of microbicides prior to intercourse is of interest if neither of the Ebola vaccines are an option. These experimental products have been used against sexually transmitted diseases, and recently polyphenylene carboxymethylene (PPCM) showed efficacy against EBOV in vitro. Shortly after, the first animal model of EBOV sexual transmission was established using type I interferon receptors (IFNAR−/−) knockout female mice in which mortality endpoint could be achieved. Here, we investigated PPCM efficacy against a mouse-adapted (ma)EBOV isolate in IFNAR−/− mice and demonstrated that 4% PPCM gel caused a 20% reduction in mortality in two distinct groups compared to control groups when inoculated prior to virus challenge. Among animals that succumbed to disease despite PPCM treatment, we report an increase in median survival time as well as a less infectious virus, and fewer virus positive vaginal swabs compared to those from vehicle-treated animals, altogether indicating the beneficial effect of using PPCM prior to exposure. A post-study analysis of the different gel formulations tested indicated that buffering the gels would have prevented an increase in acidity seen only in vehicles, suggesting that PPCM antiviral efficacy against EBOV was suboptimal in our experimental set-up. These results are encouraging and warrant further studies using optimized stable formulations with the goal of providing additional safe protective countermeasures from sexual transmission of EBOV in humans.